IMPLEMENTASI NILAI-NILAI PANCASILA DI PENGADILAN NEGERI MAKASSAR - Siti Syafira Selan; Auliah Andika Rukman; Abd. Azis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Indonesia is a country that upholds law based on Pancasila, which serves as the foundation for building a spirit of nationalism and statehood based on Pancasila values. The concept of the Indonesian rule of law is based on the legal ideals of Rechtsidee Pancasila (Article 1 paragraph (3) of the 1945 Constitution). Law also serves as a tool of social control. This study aims to determine the implementation of Pancasila values in the judicial system at the Makassar District Court. This study used qualitative research methods. The results indicate that Pancasila values have become a guideline in carrying out duties at the Makassar District Court, but their implementation has not been optimal due to the high workload and a lack of in-depth understanding of Pancasila values. The implementation of Pancasila values is influenced by internal factors such as morality, integrity, and professionalism, as well as external factors such as social pressure, caseloads, and a formalistic legal system. The implementation of Pancasila values has had a positive impact on increasing justice and public trust in the judiciary. However, this impact has not been optimal due to ongoing constraints on the legal structure and high caseloads. The research recommends that judges, clerks, and staff need to improve their understanding and internalization of Pancasila values through ongoing training and ethical development, as well as strengthening integrity and professionalism so that the implementation of Pancasila values within the judiciary can be effective and consistent.